2017
DOI: 10.1177/0043820017716683
|View full text |Cite
|
Sign up to set email alerts
|

“GRASS” ROOTS IN TEXAS: A Multiple Streams Approach to Understanding the Marijuana Movement’s Policy Impact

Abstract: Several scholars have pointed to a gap between the social movement and policy literatures, and argue that the failure of each field to incorporate the other creates a missing link in our understanding of how social movements and policy shape each other. This study provides an opportunity to make these links by applying John Kingdon's multiple streams framework of agenda setting to the marijuana movement in Texas. Texas, an unlikely candidate for marijuana reform, was the site of sustained efforts to change mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Yusuf, Neill, John, Ash, and Mahar (2016) examined the impact of political streams on climate change agenda setting, but the current research examined Political Streams on implementation of road safety policy measures. Harris and Morris (2017) used multiple stream approach to evaluate outcome of marijuana movement on political affairs at the grass-roots level in Texas, USA. Despite the presence of a well-organized campaign, the study found that political power had only a slight effect on marijuana policy.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Yusuf, Neill, John, Ash, and Mahar (2016) examined the impact of political streams on climate change agenda setting, but the current research examined Political Streams on implementation of road safety policy measures. Harris and Morris (2017) used multiple stream approach to evaluate outcome of marijuana movement on political affairs at the grass-roots level in Texas, USA. Despite the presence of a well-organized campaign, the study found that political power had only a slight effect on marijuana policy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conservative political power, reelection fears and fear of primary challenges, the fear of political retaliation, resistance among law enforcement organizations, and the general impression that existed within legislatures all contributed to the minimal influence. Harris and Morris (2017) conducted their study on Marijuana policy in the United States, an advanced democracy, but the current study examined road safety in Kenya. Helfer (2016) conducted research on the political stream, media, and agenda setting in Switzerland.…”
Section: Literature Reviewmentioning
confidence: 99%